Emergency in Malaya 1948-1960 - What was the turning point?: The case of election in Selangor - Paidi, Zulhilmi (2014)
The expansion of tin and rubber industries in Malaya resulted in an influx of Chinese and Indian immigrants.It was never thought by the British that the single society dominantly controlled by the Malays would be transformed into a multi-racial society.It was also never thought by the British, when it came to the period of decolonisation, that Malaya would face the greatest challenge with respect to nation building, compared to the other colonies. However, this view is debatable as it is believed by the Malays now that the British action was taken deliberately to fulfil the idea of colonialism.When the British claimed the need to retain the Malay status quo, they actually wanted to leave the Malays behind economically.At the same time, the foundation of a new plural society where previously a single community had dominated was a way to hold back any Malays struggle against the colonial power.1 It was clear the new ethnic diversity created tensions that were exacerbated by economic and political inequalities.This environment was conducive to the emergence of the Malayan Communist Party (MCP).2 The Communists sought to capitalise on the unrest, in order to fulfil their aim of creating a Communist Republic of Malaya.They terrorised the country and people of Malaya for twelve disastrous years, to achieve their great ambitions.It became the Communist insurrection which was one of the most important events in the history of Malaya under the British colonial rule.The insurrection was one of the toughest threats the British imperial power had ever faced in Malaya since 1824, when they officially started their colonisation of the Malay Peninsula.The insurrection, which resulted in Emergency rule, was the first British communist struggle after the end of the Second World War.One of the Malay states which experienced a severe threat from the MCP was the State of Selangor.Selangor, together with Pahang, Perak, Johor and Negeri Sembilan, were among the worst affected places during the Emergency.